Applications of digital manufacturing to steel frames: The Intermeshed Steel Connection. Issue 2 (1st September 2021) - Al‐Sabah, Salam; Laefer, Debra; Hong, Linh Truong; Huynh, Minh Phuoc; Le, Jia‐Liang; Martin, Tony; Matis, Pantelis; McGetrick, Patrick; Schultz, Arturo; Shemshadian, Mohammad E.; Dizon, Roseanne
Abstract: Despite wide use of terms such as "digital manufacturing" and "digital fabrication" in the constructional steel industry, actual use to date is mostly limited to research and development activities. In contrast, other heavy industries, such as automotive and aerospace have moved much faster and implemented many aspects of digital manufacturing and fabrication in product creation and traditional workflows. As a foil to the current state of the industry, this paper presents the erection, and disassembly of a simple, two‐storey frame that employs an alternative steel connection that can be manufactured using current plasma, laser, and water jet technologies, referred to as the intermeshed steel connection (ISC). The field demonstration described in this paper shows the connection's ability to reduce on site erection time, substantially reduce the number of site bolts, eliminate site welding, and allow for easy deconstruction. The connection has been under testing and development through a consortium of the University College Dublin, Queens University Belfast and, the University of Minnesota.